Optimizing The Implementation Of Collaborative Learning Strategies to Improve Understanding Abaut Money in Class III at SD Negeri 3 Kemiri - Walono, Gunawan (Universitas Sebelas Maret, 2022)
The research objective is the answer that will be studied in the research. This study aims to optimize the application of the collaborative learning method to increase understanding of money in class III SD Negeri 3 Kemiri. This research was conducted in 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The research subjects were teachers, 14 male students and 5 female students. Research variables include understanding, money, and collaborative learning methods. Data collection techniques used are observation and tests in the form of formative tests. The results showed that there was an increase in student understanding, teacher skills and student understanding in each cycle. Student activity in social studies learning using the Collaborative learning method cycle I with sufficient criteria, increased in cycle II with good criteria. Mastery learning in cycle I, from learning outcomes 68%, namely 11 out of 19 students with an average score of 68, while in cycle II mastery increased to 89% or 17 out of 19 students with an average of 79. The conclusion of this study is that the application of the Collaborative Learning method with worksheets can improve student learning outcomes so that it has an impact on increasing understanding of money for class III SD Negeri 3 Kemiri.